Microbial community response of nitrifying sequencing batch reactors to silver, zero-valent iron, titanium dioxide and cerium dioxide nanomaterials. (1st January 2015) - Ma, Yanjun; Metch, Jacob W.; Vejerano, Eric P.; Miller, Ian J.; Leon, Elena C.; Marr, Linsey C.; Vikesland, Peter J.; Pruden, Amy
Abstract: As nanomaterials in consumer products increasingly enter wastewater treatment plants, there is concern that they may have adverse effects on biological wastewater treatment. Effects of silver (nanoAg), zero-valent iron (NZVI), titanium dioxide (nanoTiO2 ) and cerium dioxide (nanoCeO2 ) nanomaterials on nitrification and microbial community structure were examined in duplicate lab-scale nitrifying sequencing batch reactors (SBRs) relative to control SBRs that received no nanomaterials or ionic/bulk analogs. Nitrification function was not measurably inhibited in the SBRs by any of the materials as dosing was initiated at 0.1 mg/L and sequentially increased every 14 days to 1, 10, and 20 mg/L. However, SBRs rapidly lost nitrification function when the Ag + experiment was repeated at a continuous high load of 20 mg/L. Shifts in microbial community structure and decreased microbial diversity were associated with both sequential and high loading of nanoAg and Ag +, with more pronounced effects for Ag + . Bacteroidetes became more dominant in SBRs dosed with Ag +, while Proteobacteria became more dominant in SBRs dosed with nanoAg. The two forms of silver also had distinct effects on specific bacterial genera. A decrease in nitrification gene markers ( amo A) was observed in SBRs dosed with nanoAg and Ag + . In contrast, impacts of NZVI, nanoTiO2, nanoCeO2 and their analogs on microbial community structure and nitrification gene markers were limited. TEM-EDS analysis indicated that a large portion of nanoAg remained dispersed in the activated sludge and formed Ag–S complexes, while NZVI, nanoTiO2 and nanoCeO2 were mostly aggregated and chemically unmodified. Overall, this study suggests a high threshold of the four nanomaterials in terms of exerting adverse effects on nitrification function. However, distinct microbial community responses to nanoAg indicate potential long-term effects. Graphical abstract: Highlights: Effects of nanoAg, NZVI, nanoTiO2 and nanoCeO2 on nitrifying SBRs were examined. The nanomaterials did not inhibit nitrification function from 0.1 to 20 mg/L. High-throughput pyrosequencing was used to characterize the response of activated sludge microbial communities to nanomaterials. Distinct effects of nanoAg and Ag + on microbial community structure were observed. NanoAg and Ag + both decreased microbial diversity and abundance of nitrification gene markers.